2019
DOI: 10.2147/dmso.s213643
|View full text |Cite
|
Sign up to set email alerts
|

<p>Relationship Between Skeletal Muscle Mass Indexes and Muscular Function, Metabolic Profile and Bone Mineral Density in Women with Recommendation for Bariatric Surgery</p>

Abstract: Background and aim: We evaluated low skeletal muscle mass (LMM) in women prior to bariatric surgery (BS) through different skeletal muscle mass indexes (MMIs) regarding body fat percentage (BFP), handgrip strength (HS), six-minute walk test (6MWT), metabolic profile and bone mineral density (BMD). Methods: Women (n=62) were allocated into two groups according to LMM: obesity with low muscle mass (OLMM) or obesity with normal muscle mass (ONMM). LMM was defined by the appendicular skeletal muscle mass (ASM) adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…In the present study, we observed that the mean 6MWD in the total sample and the mean 6MWD in the class 3 obesity group were 428.3±85.7 m and 417.3±76.4 m, respectively. These values were slightly higher than those reported by Crispim Carvalho et al ( 20 ) in 62 obese women aged 24-57 years but close to those observed by Vargas et al ( 21 ) in a cohort of 67 obese individuals, including 61 (91%) women and 6 (9%) men, with a mean age of 38±10 years. Differences in the metabolic profile of the sampled population, the type and frequency of incentives, and the length of the corridor may explain the differences reported in 6MWD; therefore, these factors should be considered when interpreting the results ( 21 ).…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, we observed that the mean 6MWD in the total sample and the mean 6MWD in the class 3 obesity group were 428.3±85.7 m and 417.3±76.4 m, respectively. These values were slightly higher than those reported by Crispim Carvalho et al ( 20 ) in 62 obese women aged 24-57 years but close to those observed by Vargas et al ( 21 ) in a cohort of 67 obese individuals, including 61 (91%) women and 6 (9%) men, with a mean age of 38±10 years. Differences in the metabolic profile of the sampled population, the type and frequency of incentives, and the length of the corridor may explain the differences reported in 6MWD; therefore, these factors should be considered when interpreting the results ( 21 ).…”
Section: Discussionsupporting
confidence: 80%
“…Despite the importance of the 6 MWT, research on its value for the obese population is limited. In addition, almost all previous studies involving the 6 MWT have been performed in samples predominantly composed of obese women, who have very different performance from that observed in obese men during submaximal exercise [ 3 , 6 , 11 , 19 , 21 ]. Similar to Wooldridge et al [ 4 ], Vanhelst et al [ 22 ], and Hulens et al [ 23 ], we observed that BMI was one of the most important variables in the reference equation for the 6 MWD of obese subjects, which is not surprising because excess weight increases the workload and affects walking due to trunk oscillation and the increased distance between the feet [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, without previous studies, it is difficult to draw some parallel [56]. Different clinical outcomes, such as increased risk of developing metabolic syndrome, difficulties in performing daily living activities of and mortality are related to muscle mass and low quality of muscle functions [35,68,69]. Recent evidence shows that low quality muscle mass is associated with the development of frailty in obese individuals [70].…”
Section: Discussionmentioning
confidence: 99%